A)

$\displaystyle y'=\frac{x^{3}-y}{x+y^{3}}$

B)

$\displaystyle (2y+1)dx+(\frac{x^{2}-y}{x})dy=0$

how to eproach them

?

Printable View

- Nov 13th 2010, 06:07 AMtransgalacticfractured mixed equations
A)

$\displaystyle y'=\frac{x^{3}-y}{x+y^{3}}$

B)

$\displaystyle (2y+1)dx+(\frac{x^{2}-y}{x})dy=0$

how to eproach them

? - Nov 13th 2010, 07:05 AMFernandoRevilla
- Nov 13th 2010, 07:13 AMtransgalactic
what abou B

- Nov 13th 2010, 07:19 AMFernandoRevilla
It has an integrating factor that depends on $\displaystyle x$

Regards.